Comparison of Day 14 Serum Progesterone Level Based on Pregnancy Outcome in Patients Undergoing Intracytoplasmic Sperm Injection Cycles - Marzieh Mehrafza; Azadeh Raouf; Talieh Rahimian; Zahra Nikpouri; Parvaneh Abdollahian; Ahmad Hosseini (Journal of Kerman University of Medical Sciences, 2015)
Background & Aims: Serum progesterone level (as early as 4 weeks gestation) reflects the relation between embryo and corpus luteum. The purpose of the present study was to compare serum progesterone level on day 14 after embryo transfer among 3 groups of patients undergoing intracytoplasmic sperm injection (ICSI) cycles; normal pregnancy (viable intrauterine pregnancy), abnormal pregnancy (miscarriage, ectopic, and biochemical pregnancy), or nonpregnant. Methods: In the present study, 103 patients undergoing ICSI, were retrospectively analyzed. They were divided into 3 groups according to pregnancy outcome; normal pregnancy, abnormal pregnancy, and nonpregnant. Baseline and stimulation characteristics and day 14 progesterone level of patients were compared among groups. Results: Day 14 serum progesterone levels were significantly different among groups; 54.3 ng/ml in normal pregnancy, 39.8 ng/ml in abnormal pregnancy, and 26.2 ng/ml in nonpregnant groups (P < 0.001). No significant differences were observed among the groups in terms of age (P = 0.081), BMI (P = 0.247), baseline follicle-stimulating hormone (FSH) (P = 0.133), and baseline anti-Mullerian hormone (AMH) (P = 0.576), male factor infertility (P = 0.790), total number of retrieved oocyte (P = 0.891), metaphase II oocytes (P = 0.918), and estradiol level on the day of human chorionic gonadotropin (HCG) or human menopausal gonadotropin (HMG) administration (P = 0.838). We determined the 39.5 ng/ml progesterone concentration as the cut-off point with 62% sensitivity and 69% specificity. Conclusion: Despite using the same dose of progesterone supplements, day 14 serum progesterone level was significantly higher in women who achieved normal pregnancy after ICSI compared with others.